Investment in rural development programmes. Its territorial distribution in the province of Granada - Cejudo García, Eugenio; Navarro Valverde, Francisco Antonio (Anales de Geografía de la Universidad Complutense, 2010)
Initiatives LEADER I, II and +, as well as PRODER I and II Programs have produced benefits in rural zones were they have been developed, for instance the province of Granada. Nevertheless, there have been other undesirable effects derived from them such as investment territorial distribution, which has favoured the most dynamics councils, or the limited role of public investment redistribution. As a consequence territorial and social disparities have been remarked favouring regional center and the most active municipalities thus restricting the access to these aids of peripheral towns which continue suffering drift from the land.
Keywords: Initiatives LEADER I; II and; PRODER I and II Programs; Public investment; Social and territorial inequalities; Rural development